Female Seclusion in the Aftermath of Slavery on the Southern Swahili Coast: Transformations of Slavery in Unexpected Places - Becker, Felicitas (The International journal of African historical studies, 2015)
[...]it is intimately tied to the question of the silence or guarded, coded speech surrounding slavery.\n Our conversations took place about eighty years after official abolition in Tanganyika, and about a hundred years after slave labor regimes had begun to crumble, but, as the preceding ages have sought to show, the memory of slavery surrounded them when they grew up. [...]I think it is important to identify reasons why social memory should, on certain questions, depart from or skew the facts, such as the status implications of slave antecedents discussed above, which made owning up to such antecedents problematic.